Dual Channel Endoscopic Mucosal Resection - Saraidaridis, Julia T.; Gaetani, Racquel S.; Marcello, Peter W. (Clinics in Colon and Rectal Surgery, 2023)
Endoscopic mucosal resection (EMR) is the recommended technique for colon polypectomy for nonpedunculated lesions that are >20 mm in size not requiring excision. Dual-channel EMR (DC-EMR) uses an endoscope with two working channels to facilitate easier submucosal injection, snare resection, and clip closure of polypectomy defects. There is also promising early literature indicating that this endoscopic modality can reduce the overall learning curve present for single-channel colonoscopy EMR. This chapter will describe the steps and techniques required to perform DC-EMR, potential complications, recommended postprocedure surveillance, and future directions.
Keywords: EMR; dual-channel EMR; single-channel EMR; endoluminal surgery